2006
DOI: 10.1292/jvms.68.21
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of a Group 2 Coronavirus in Dogs in Japan

Abstract: ABSTRACT. Canine coronavirus (CCoV) has been reported to cause acute diarrhea mainly in young pups. CCoV and feline coronavirus are classified as group 1 coronaviruses. However, it has recently been reported in the United Kingdom that the group 2 coronavirus gene, which is more closely related to the bovine coronavirus (BCoV) and human coronavirus strain OC43, has been detected in respiratory tract tissue samples from dogs with respiratory disease. In this study, we examined the prevalence of antibodies to gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 9 publications
3
48
0
Order By: Relevance
“…Group 2 CRCoV, recently isolated in England as a new ITB pathogen closely related to bovine coronavirus [20], was again found to be associated with the diseased puppy in the present study. CRCoV infection was already confirmed in Japanese domestic dogs both seroepidemiologically [26] and molecular epidemiologically [43]. The present No.…”
Section: Discussionsupporting
confidence: 59%
“…Group 2 CRCoV, recently isolated in England as a new ITB pathogen closely related to bovine coronavirus [20], was again found to be associated with the diseased puppy in the present study. CRCoV infection was already confirmed in Japanese domestic dogs both seroepidemiologically [26] and molecular epidemiologically [43]. The present No.…”
Section: Discussionsupporting
confidence: 59%
“…Erles et al [5] designated this unknown group 2 coronavirus canine respiratory coronavirus (CRCoV), which is considered to be one of the major pathogens of canine infectious respiratory disease (CRID), like canine parainfluenza virus (CPIV), canine adenovirus type 2 (CAV-2), and the bacterium Bordetella bronchiseptica [3][4][5]. We also reported that the known group 1 coronaviruses (CCoV) that cause enteritis and an unknown group 2 coronavirus were prevalent in domestic dogs in Japan [8]. Compatible results in a survey of dogs in Japan for group 2 canine coronavirus infection were also reported by Yachi and Mochizuki [18].…”
mentioning
confidence: 92%
“…To date, few CRCoV strains have been isolated from a small number of countries: the United Kingdom (n=2), Japan (n=2), Italy (n=1), and Korea (n=3) [1,6,12,17]. Antibodies against CRCoV are common in canine populations in the United Kingdom (36.2%), Republic of Ireland (30.3%), USA (54.7%), Japan (17.8%), Italy (32.1%), and New Zealand (29%) [4,9,10,13].…”
mentioning
confidence: 99%